Control Of Bidirectional DC-DC Converter For Battery Storage System In Grid-Connected Quasi-Z-Source PV Inverter - Zulhani, Rasin; M.F., Rahman (Institute Of Electrical And Electronics Engineers Inc. (IEEE), 2016)
The use of bidirectional DC-DC converter to interface battery energy storage system with the conventional PV inverter system has been widely addressed. It is however has never been considered to be integrated with the quasi-Z-source inverter (qZSI) topology, which offers several advantages e.g. a single stage buck-boost conversion. This paper specifically discusses on the development of the controller to realize a bidirectional power flow control for the DC-DC converter attached to the grid-connected PV based qZSI using the proposed battery storage method. Based on the circuit analysis, current-to-control relation is established, and results from both simulation and experiment demonstrates the proposed method works according to the requirement.